Experimental investigation on shear behavior of steel beam-to-CFST column connections with irregular panel zone. (1st August 2018) - Mou, Ben; Bai, Yongtao
Highlights: Experimental study of a new steel beam-to-CFST column connection was conducted. The new connection consists of unequal depth beams and CFST column. Seismic shear behavior of the irregular panel zones was investigated. Complex failure modes were distinguished in various panel locations. Abstract: This paper presents an experimental investigation on the seismic behavior of a novel steel-concrete composite beam-to-column connections reinforced by outer-annular-stiffener. This type of connection consists of beams with varying depths in opposite sides, and a concrete filled steel tubular (CFST) column. Four cruciform connection specimens with varying beam depth ratios (1, 0.75 and 0.5) were tested under monotonic and cyclic loading protocols to investigate shear capacity, hysteretic behavior, deformation capacity and failure modes within the irregular joint panel zone. From the test results, two types of failure modes were identified as global shear failure occurred in the panel zones 1 and 2 on the side of large depth beam when subjected to positive loading direction, and partial shear failure only in the panel zone 1 under the negative loading direction. The global shear failure was characterized by plastic deformation in the panel zones 1 and 2 prior to out-of-plane instability arose in the column flange near the outer-annular-stiffener. On the other hand, shear failure of panel zone under negative direction loading, the deformation of steel part was similar to that under the positive loading direction. While, the concrete panel zone located in the web of column only connecting with small depth beam, showed an arch mechanism. There was no fatigue fracture throughout the test, and all the specimens behaved in a ductile manner. All the tested specimens demonstrated good plastic deformation and energy dissipation capacity.